Validation of low-cost eye tracking setup for smooth pursuit application - Che Azemin, Mohd Zulfaezal; Mohd Tamrin, Mohd Izzuddin; Arshad, Awatif Akmal (IEEE, 2014)
Eye movement can systematically facilitate the detection of brain activities for the discovery of neurologic diseases. However, the traditional techniques such as electrooculography requires expensive equipments, technical handling skills and fairly invasive. This research work aims to test the validity of the low-cost smooth pursuit experimental setup to track eye movement when presented with different stimuli. The setup is constructed based on open system concept.